Unique lymphocyte transcriptomic profiles in septic patients with chronic critical illness - Barrios, Evan L.; Balzano-Nogueira, Leandro; Polcz, Valerie E.; Rodhouse, Christine; Leary, Jack R.; Darden, Dijoia B.; Rincon, Jaimar C.; Dirain, Marvin L.; Ungaro, Ricardo; Nacionales, Dina C.; Larson, Shawn D.; Sharma, Ashish; et al. (Frontiers in Immunology, 2024)
IntroductionDespite continued improvement in post-sepsis survival, long term morbidity and mortality remain high. Chronic critical illness (CCI), defined as persistent inflammation and organ injury requiring prolonged intensive care, is a harbinger of poor long-term outcomes in sepsis survivors. Current dogma states that sepsis survivors are immunosuppressed, particularly in CCI. Investigation of this immune suppression in heterogeneous immune populations across distinct clinical trajectories and outcomes, along with limited sampling access, is accessible via single-cell RNA sequencing (scRNA-seq).MethodsscRNA-seq analysis was performed on healthy subjects (n=12), acutely septic patients at day 4 ± 1 (n=4), and those defined as rapid recovery (n=4) or CCI (n=5) at day 14-21. Differential gene expression and pathway analyses were performed on peripheral blood lymphocytes at both a population and annotated cell subset level. Cellular function was assessed via enzyme-linked immunosorbent spot (ELISpot), cytokine production analysis, and T-cell proliferation assays on an additional cohort of septic patients (19 healthy, 68 acutely septic, 27 rapid recovery and 20 classified as CCI 14-21 days after sepsis onset).ResultsSepsis survivors that developed CCI exhibited proportional shifts within lymphoid cell populations, with expanded frequency of CD8+ and NK cells. Differential expression and pathway analyses revealed continued activation in T cells and NK cells, with generalized suppression of B-cell function. Both T and NK cell subsets displayed transcriptomic profiles of exhaustion and immunosuppression in CCI, particularly in CD8+ T effector memory (TEM) cells and NK cells. Functional validation of T-cell behavior in an independent cohort demonstrated T cells maintained proliferative responses in vitro yet exhibited a marked loss of cytokine production. IFN-γ production at the acute phase (day 4 ± 1) was significantly reduced in subjects later classified as CCI.DiscussionSepsis patients exhibit unique T-, B-, and NK-cell transcriptional patterns that are both time- and clinical trajectory-dependent. These transcriptomic and pathway differences in sepsis patients that develop CCI are associated with exhaustion in CD8+ TEM cells and NK cells. Understanding the specific immune system patterns of different cell subsets after sepsis at a molecular level will be key to the development of personalized immunotherapy and drug-targeting intervention.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT02276417.